1990
DOI: 10.1139/v90-025
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of 7-azaindole, an unusual hydrogen-bonded tetramer, and of two of its methylmercury(II) complexes

Abstract: 90.71(3)", Z = 16, R = 0.052) contain tetrameric units of approximate S4 symmetry, in which the molecules are associated by means of four complementary N-H.. . N hydrogen bonds. [CH3Hg(7-azaindole)]N03 (P1 , a = 7.818(3), b = 7.884(3), c = 9.135(4) A, a = 97.89(3), P = 109.13(3), y = 103.28(3)", Z = 2, R = 0.039) contains well-separated nitrate ions and complex cations in which the methylmercury group is linearly bonded to the pyridine nitrogen atom, whereas the five-membered rin remains protonated. In the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 12 publications
2
42
0
Order By: Relevance
“…Ligands 1 and 4 each form qne moderately strong (38) hydrogen bond (N...CI < 3.13 A) with a single chlorine. This corresporids to relatively small N(l 1)-N(17)-Cu(1)-Cl (1) and N(41)-N(47)-Cu(4)-Cl(4) torsion angles of 39.1(3) and 33.7(3)', respectively. For ligands 2 and 3, the torsion angles are close to 60°, so that the N-H bonds are roughly equidistant from two chlorines, with which they form bifurcated hydrogen bonds.…”
Section: C1(3)cu(l)c1(2)cu(2)c1(3) Chain Ismentioning
confidence: 89%
“…Ligands 1 and 4 each form qne moderately strong (38) hydrogen bond (N...CI < 3.13 A) with a single chlorine. This corresporids to relatively small N(l 1)-N(17)-Cu(1)-Cl (1) and N(41)-N(47)-Cu(4)-Cl(4) torsion angles of 39.1(3) and 33.7(3)', respectively. For ligands 2 and 3, the torsion angles are close to 60°, so that the N-H bonds are roughly equidistant from two chlorines, with which they form bifurcated hydrogen bonds.…”
Section: C1(3)cu(l)c1(2)cu(2)c1(3) Chain Ismentioning
confidence: 89%
“…The validity of the computational methods used in this paper is provided by comparison of theoretical results with molecular structures and properties of the 7AI monomer that have been measured experimentally. The molecular geometries of 7AI monomer and dimer are both unknown, as the x-ray diffraction studies have revealed that 7AI forms a tetramer in the crystal state (18). Only the 7AI monomer rotational constants and the position of its pyrrole proton in the inertial axis frame are known in the gas phase (19).…”
Section: The Three Defining Simultaneity Principles Of Photo-induced mentioning
confidence: 99%
“…(Table s-313, are not significantly different. N7-C6 coupling does not appreciably affect bond lengths and angles in the azaindolyl unit, but greater differences are found in the azaindolium ring (14). The bond lengths are increased by -0.02 A in the C(16)-N(17)-C(18)-C (19) region, whereas N(l1)-C (18) is shortened by the same amount.…”
Section: Reactants and Techniquesmentioning
confidence: 78%
“…The formally neutral 7-azaindole ligands is bonded via N7. The distances and angles in coordinated azaindole (Table 5) show no significant differences with those found in free azaindole and other complexes containing monodentate N7-bonded azaindole (14,16,(18)(19)(20). The ligand two-ring system is planar: the mean atom-to-plane distance (0.0!2 A) corresponds to l a with the largest deviation (0.023(10) A) found for N(7) (Table S-4)3.…”
Section: Reactants and Techniquesmentioning
confidence: 86%
See 1 more Smart Citation